Extracellular matrix: the gatekeeper of tumor angiogenesis. (11th October 2019) - Mongiat, Maurizio; Buraschi, Simone; Andreuzzi, Eva; Neill, Thomas; Iozzo, Renato V.
Abstract: The extracellular matrix is a network of secreted macromolecules that provides a harmonious meshwork for the growth and homeostatic development of organisms. It conveys multiple signaling cascades affecting specific surface receptors that impact cell behavior. During cancer growth, this bioactive meshwork is remodeled and enriched in newly formed blood vessels, which provide nutrients and oxygen to the growing tumor cells. Remodeling of the tumor microenvironment leads to the formation of bioactive fragments that may have a distinct function from their parent molecules, and the balance among these factors directly influence cell viability and metastatic progression. Indeed, the matrix acts as a gatekeeper by regulating the access of cancer cells to nutrients. Here, we will critically evaluate the role of selected matrix constituents in regulating tumor angiogenesis and provide up-to-date information concerning their primary mechanisms of action.